Bisphenol A (BPA) the mighty and the mutagenic. (2018) - Jalal, Nasir; Surendranath, Austin R.; Pathak, Janak L.; Yu, Shi; Chung, Chang Y.
Graphical abstract: Highlights: Measurement of BPA in human tissues and organs is critically analyzed. The tumorigenic effects of low and high dose BPA in-vitro and in-vivo experiments discussed. BPA induced DNA damage and activation of signaling pathways that initiate tumorigenic changes in target cell have been discussed. New experimental approaches to evaluate the carcinogenic potential of BPA proposed. Abstract: Bisphenol A (BPA) is one of the most widely used synthetic compounds on the planet. Upon entering the diet, its highest concentration (1–104 ng/g of tissue) has been recorded in the placenta and fetus. This accumulation of BPA can have many health hazards ranging from the easy to repair single strand DNA breaks (SSBs) to error prone double strand DNA breaks (DSBs). Although the Human liver can efficiently metabolize BPA via glucuronidation and sulfation pathways, however the by-product Bisphenol -o- quinone has been shown to act as a DNA adduct. Low doses of BPA have also been shown to interact with various signaling pathways to disrupt normal downstream signaling. Analysis has been made on how BPA could interact with several signaling pathways such as NFκB, JNK, MAPK, ER and AR that eventually lead to disease morphology and even tumorigenesis. The role of low dose BPA is also discussed in dysregulating Ca 2+ homeostasis of the cell by inhibiting calcium channels such as SPCA1/2 to suggest a new direction for future research in the realms of BPA induced disease morphology and mutagenicity.